Synthesis of aculeatins A and B via iterative hydrolytic kinetic resolution - Harbindu, Anand; Kumar, Pradeep (Synthesis-Stuttgart, 2010)
A simple and concise approach for the synthesis of aculeatins A and B starting from (+/-)-epichlorohydrin is described. The synthetic strategy features Jacobsen's hydrolytic kinetic resolution and a Linchpin coupling as key steps.
Keywords: aculeatins; Epoxide; Hydrolytic kinetic resolution; Linchpin coupling; spirocyclization